PENGARUH KOMPETENSI AUDITOR DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN SKEPTISME PROFESIONAL SEBAGAI VARIBEL INTERVENING - Hendar Muhammad Rifoaffa; Asri Zaldin (Lembaga Penelitian Universitas Trisakti, 2020)
The perfection of audit quality can be achieved through the performance results of competent auditors. This research aims to determine the effect of auditors competence, and independence on the audit quality. This research was conducted at Jakarta in 2019. The population of this research is a public accounting of Jakarta Pusat by spreading questionnaire directly to the Respondents. Respondents in this study were 40 auditors working at public accounting firms. Research using primary data, Analysis of the data used is Statistical Package for the Social Sciences (SPSS). The results of this study indicate that the competency and independency affect the auditor's ability to detect fraud through professional skepticism positively.